Perancangan Dan Implementasi Kecerdasan Buatan Menggunakan Algoritma String Matching Pada Prototype Filtering Asap Berbasis Mikrokontroler AVR Atmega 32A - Wan Hendra Manihuruk; Budi Purnomo; Saharudin (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2020)
The pollution was became an important issued that would be threaten human life. The human being activities that cause becoming pollution. Therefore, the monitoring level of pollution needed to determine for pollution index in the area, in order to maintain pollutant level in the lower value. To find out of the fume level is used MQ-2 fume censor that could be sensitive toward to air quality and and the view of index is used LCD and according software with serial communication that previously processed by microcontroller. This system expected to be able provide solution against pollution problems because the affordable cost compared from environmental agency equipment. The designing and intelligence of implementation synthetic used algoritma string matching based of the fume prototype filtering microcontroller ATmega 32A is implemented according of needs analysis with use arduino language programing. Arduino as language programing microcontroller and eclipse to made android application.